Fikrah Sanksi Pidana Atas Pelaku Pernikahan Di Bawah Tangan - Mariani Mariani (Fakultas Syariah UIN Antasari, 2021)
Abstract: In constitution number 1 of 1974, it is stated that the marriage is legal if conducted in accordance with the law of each personâ€™s religion and faith, and every marriage has to be registered in accordance withÂ applicable laws and regulations. In fact, there are some practices of marriage that are conducted only using religious law, fulfiling its requirements and pillars, but it is not registered at the the authorized institution. It is called â€œunderhand marriageâ€. Whereas Sirri marriage is the hidden or secret marriage. There is controversion about the legitimacy of the two kinds of marriage. There is an opinon stating that the marriage is legal if it fulfils the pillars and requirements. Another opinion states that registration is a part from marriage as an authentic proof and legally enforceable. This research uses descriptive qualitative method, so results have been found in the form of communityâ€™s review who accept secret marriage with its arguments, and on the other hand, who reject secret marriage. Besides, the analysis of criminal sanction that threatens secret marriage and efforts to overcome the secret marriage. This article also discusses about the secret/ underhand marriage, its history, and its criminal sanction.Â Abstrak: Undang Undang No 1 Tahun 1974 tentang perkawinan disebutkan bahwa perkawinanÂ sah apabilaÂ dilaksanakan menurutÂ hukum masing masing agama dan kepercayaan dan setiap perkawinan harus dicatatÂ menurut peraturan perundangan yang berlaku. Faktanya di masyarakat ditemukan terjadi perkawinan yang hanya dilaksanakan secara agama dan memenuhi syarat dan rukunnya tapi tidakÂ dicatatkan pada lembaga yang berwenang ini disebut perkawinan di bawah tangan. Adapun perkawinan sirri adalah perkawinan yang disembunyikan atau rahasia. Terjadi kontroversi silang pendapat tentang sah tidak nyakedua perkawinan tersebut. Ada pendapat yang mengatakan perkawinan tersebutÂ sah apabila terpenuhi rukun dan syaratnya, tapi ada yang berpendapat pencatatan adalah bagian yang tak terpisahkanÂ dari perkawinan sebagai bukti otentik dan berkekuatan hukum. Metode yang digunakan dalam penelitian ini yaituÂ deskriptif kualitatif, sehingga didapatkan hasil temuan yaitu review masyarakat yang menerima nikah sirri dengan argumennya, dan masyarakat yang menolak nikah sirri. Juga analisisÂ sangsi pidana yang mengancam nikah sirri dan upaya mengatasiÂ nikah sirri. Artikel ini juga membahas terkaitÂ perkawinanÂ sirri/di bawah tangan, serta sejarahÂ dan sanksi pidana pada nikah sirri.